TOWARDS A THEORETICAL MODEL OF APOROPHOBIA - Picado-Valverde, Eva María; Guzmán-Ordaz, Raquel; Yurrebaso-Macho, Amaia (Acciones e Investigaciones Sociales, 2022)
Currently, aporophobia is acquiring greater visibility due to the influence of changes in Spanish legislation, such as Organic Law 8/2021, of 4 June, on the comprehensive protection of children and adolescents against violence. The role of social workers in the face of rejection and aggression towards the poor is crucial, since attention to these people is a priority in the social sphere, and the challenge is to provide comprehensive intervention to eliminate aporophobia. Given the lack of specific theoretical models on aporophobia, this article examines different comprehensive theories that will facilitate the explanation of this phenomenon, such as the elements involved in the discriminatory process towards these people, the explanatory factors of the aggressors' group behaviour towards the victims of aporophobia and the intersectional model that explains, in an interactional way, the inequalities and discrimination towards them.The aim is to develop effective strategies and action plans that facilitate the intervention of social workers, especially in the detection of these victimisations.
Keywords: Aporophobia, discrimination against the poor, social exclusion, prejudice, poverty.